Pelesapan Morfem Pada Tuturan Minang Kabau: Suatu Kajian Morfologi - Johan, Mhd (Asosiasi Ide Bahasa Kepri, 2024)
The research aims to look for Minangkabau speech events spoken by Minangkabau residents living in Batam using a morphological approach. Then the researcher used Johan's theory which was related to his previous research which was published in the Alfabeta journal and was supported by Johan's other theories. Then, in collecting data, researchers used the contribution method using the expert listening and involvement technique which was initiated by Sudaryanto and supported by Nadra's theory in the form of the fishing rod technique. To analyze the data, researchers used a technique for direct elements, where this technique directly analyzes the words produced by respondents. After the data was analyzed, results were obtained. The results obtained were the occurrence of phoneme deletions in speech. The syllables are 4 times at the beginning of the syllable with a percentage of 36%, in the middle of the syllable 1 time with a percentage of 9%, at the end of the syllable 1 time with a percentage of 9% and utterances that do not contain syllables 5 times with a percentage of 45% . Words that do not contain punctuation consist of basic words and affixes.